Prevalence of Aflatoxin M1 in Milk of Bovine in and around Junagadh, Gujarat State of India - Hedpara, Jay R.; Sindhi, Samiulla H.; N., Sanjay; Kumar, Binod; Bhedi, Kirit R. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Aflatoxin M1 (AFM1) is a hydroxylated metabolite of aflatoxin B1 from a contaminated feed. Aflatoxins are toxic, mutagenic and carcinogenic compounds produced as a secondary metabolite by the fungi Aspergillus flavus and A. parasiticus. The present study was conducted to determine the prevalence of AFM1 in milk by using two different diagnostic methods, viz., Enzyme-Linked Immunosorbent Assay (ELISA) and Lateral Flow Assay (LFA). A total of 200 milk samples were collected from the areas under Junagadh city and nearby villages. An overall 93.5% incidence rate of AFM1 contamination in milk samples was recorded. Out of 200 samples, 6 (3%) samples were found to contain AFM1 above the FSSAI standard limit (0.5 µg/L) and 145 (72.5%) samples had AFM1 above the standard limit as per EU legislation (0.05 µg/L). Out of total 200 samples, 50 representative samples ana